The last supper club : a waiter's requiem - Batt, Matthew C. (University of Minnesota Press, 2023)
"The story of how Matthew Batt, a forty-something professor on sabbatical, found himself returning to a job waiting tables. And loving it. In this rare and vivid memoir, he details the challenge and satisfaction of meeting the demands of a fine dining restaurant's frenzied kitchen and equally expectant crowd. Told with sharp humor, humility, and a keen sense of what matters, The Last Supper Club is an ode to working in restaurants, the relationships that get you to the night's close, and finding yourself through-or perhaps because of-the chaos of it all"--